Switched Capacitor Nine-level inverter with reduced components for Grid connected PV systems using Fuzzy logic controller - Hania Aboub; Rabiaa Mechouma; Boubekeur Azoui (International Journal of Energetica)
The novel use of a three-phase switched capacitor SC nine-level inverter in a PV system is described in this article. It has a low input voltage, fewer components, and is grid-connected. The primary benefit of the suggested inverter is high voltage gain, which is attained by switching capacitors in series and parallel to raise the output voltage with the proper switching management. It is simpler to design a fuzzy logic controller to increase the infusion of solar energy into the electrical network. The MATLAB/Simulink environment's findings demonstrate that the suggested fuzzy logic controller performs well under a range of illumination levels. In comparison to the traditional PI controller, the total harmonic distortion (THD) obtained is less than the limit of 0.67 %. Good spectrum analysis and strong performance with fewer components are made possible by the nine-level SC inverter.